2023
DOI: 10.1039/d3sm00333g
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-dependent anomalous viscosity of aqueous solutions of imidazolium-based ionic liquids

Abstract: Ionic liquids (ILs) are organic salts with a low melting point compared to any inorganic salts. The room temperature ILs are of great importance for their widespread potential industrial applications....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 93 publications
(126 reference statements)
0
1
0
Order By: Relevance
“…The class of salts known as ILs is made up of cations and anions and is distinguished by its distinct physicochemical properties, typically possessing a melting point at or below 100 °C. These flexible and environmentally friendly molecules offer a wide range of potential applications in IL-based technologies owing to their nonvolatility, high recovery rates, and diverse range of advantageous characteristics. ,, The interaction between DNA and ILs has recently seen a significant increase in research activity due to the wide range of potential applications in areas like drug delivery, gene therapy, and biosensors. Jumbri et al demonstrated the binding mode of imidazolium-based ILs ([C n bmim]Br where n = 2,4,6) with calf thymus DNA using molecular docking and fluorescence experiments . Chandran et al shed light on the atomistic mechanisms underlying the exceptional stability displayed by DNA in ILs in a separate study.…”
Section: Introductionmentioning
confidence: 99%
“…The class of salts known as ILs is made up of cations and anions and is distinguished by its distinct physicochemical properties, typically possessing a melting point at or below 100 °C. These flexible and environmentally friendly molecules offer a wide range of potential applications in IL-based technologies owing to their nonvolatility, high recovery rates, and diverse range of advantageous characteristics. ,, The interaction between DNA and ILs has recently seen a significant increase in research activity due to the wide range of potential applications in areas like drug delivery, gene therapy, and biosensors. Jumbri et al demonstrated the binding mode of imidazolium-based ILs ([C n bmim]Br where n = 2,4,6) with calf thymus DNA using molecular docking and fluorescence experiments . Chandran et al shed light on the atomistic mechanisms underlying the exceptional stability displayed by DNA in ILs in a separate study.…”
Section: Introductionmentioning
confidence: 99%